Analysis of the Progress and Optimization Path of Digitization of Corporate Policy Services in China - Mei, Jiaqi; Qi, Xiangyu (International Journal of Global Economics and Management, 2024)
With the rapid development of information technology, the digital transformation of China’s corporate policy services has become a key factor in driving corporate innovation and economic growth. Studies have pointed out that digitized policy services have effectively improved policy transparency and the ease of access to policy information for enterprises, while also providing them with a more efficient and precise way to file policy declarations. However, challenges such as information silos, data security and privacy protection still exist in the digitization process. The article further discusses the optimization path and suggests measures such as strengthening cross-departmental data sharing, improving laws and regulations, and enhancing enterprises’ digital literacy in order to promote the healthy development of policy service digitization. This study provides valuable references for government departments and enterprises, and is of great significance in promoting the digital transformation of corporate policy services in China.